2007
DOI: 10.1002/tl.272
|View full text |Cite
|
Sign up to set email alerts
|

The permeable and impermeable wall of expectations

Abstract: This chapter presents an autoethnography of a Chinese American woman's twenty‐five years of experience in higher education at universities in Southern California and the Pacific Northwest. Her career is discussed in four stages: master's teaching assistant and student, part‐time instructor, doctoral teaching assistant and student, and professor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Professorial authority and subject-matter credibility. Narrative research (e.g., Fong, 2007;Ford, 2011;Han, 2011aHan, , 2012Lin et al, 2006;McLean, 2007;Muhtaseb, 2007;Vargas, 1999) has reported that students, faculty, and administrators have shown difficulty accepting WFOC as credible experts and scholars in their academic fields. When WFOC teach race, social justice, or multicultural education, White students resist course content as if WFOC brought with them political agendas rather than academic content and global education (Han, 2013;Perry et al, 2009;Vargas, 1999).…”
Section: Women Faculty Of Color: Gendered and Racialized In Academiamentioning
confidence: 99%
See 2 more Smart Citations
“…Professorial authority and subject-matter credibility. Narrative research (e.g., Fong, 2007;Ford, 2011;Han, 2011aHan, , 2012Lin et al, 2006;McLean, 2007;Muhtaseb, 2007;Vargas, 1999) has reported that students, faculty, and administrators have shown difficulty accepting WFOC as credible experts and scholars in their academic fields. When WFOC teach race, social justice, or multicultural education, White students resist course content as if WFOC brought with them political agendas rather than academic content and global education (Han, 2013;Perry et al, 2009;Vargas, 1999).…”
Section: Women Faculty Of Color: Gendered and Racialized In Academiamentioning
confidence: 99%
“…As such, WFOC perceive that White students expect the "normal," prototype professor (i.e., [fe]male from a mainstream background with Euro American cultural capital, standard English speech patterns, white skin, Euro American attire, and interactional demeanor) for their college experience (Han, 2011a(Han, , 2012Ford, 2011;Vargas, 1999). When their professors happen to be Asian women, their professorial authority is undermined and credibility questioned, White students tend to avoid the courses offered by WFOC (Fong, 2007;Ford, 2011), and they complain to senior or other White faculty and administrators about WFOC's poor teaching and accents (Han, 2011a(Han, , 2012.…”
Section: Women Faculty Of Color: Gendered and Racialized In Academiamentioning
confidence: 99%
See 1 more Smart Citation